IRAC's Insecticide Mode of Action Classification - Frederick M. Fishel (EDIS)
This revised 6-page fact sheet explains the rationale behind the Insecticide Resistance Action Committee's (IRAC) insecticide and acaricide mode of action classification and provides a listing of those insecticide common names with their groupings and primary modes of action for insecticides currently registered in Florida. Written by Frederick M. Fishel and published by the UF Department of Agronomy, April 2011.